Students argumentation quality and argumentation skill biology education student - Astuti Muh Amin; Romi Adiansyah; Noor Hujjatusnaini (JURNAL BIOEDUKATIKA, 2021)
The ability to give arguments is very essential for students in order that they can take more roles in various aspects of life. The quality of students' arguments can be reflected in their ability to accommodate higher-order thinking skills to generate an argument. This study aims at analyzing students ability to make arguments and the quality of their arguments after the implementation of Reading, Questioning and Answering (RQA), ADI (Argument-Driven Inquiry), RQA integrated with ADI, and conventional learning strategies. This research is a survey research using a descriptive quantitative approach. The subjects of this research were the Biology Education students of UIN Alauddin Makassar and Universitas Muslim Maros, South Sulawesi, consisting of 92 students. The collected data were in the form of students argumentation skill data obtained from the observation sheets in each class through the implementation of RQA strategy, ADI strategy, RQA integrated with ADI strategy, and conventional learning strategy on animals Physiology learning. The results of this research showed that the quality of students' arguments at the implementation of RQA, ADI, RQA integrated with ADI learning strategies was at the level of application, analysis, evaluation, and creation, while at the implementation of conventional learning their argumentation quality was at the level of memorizing and understanding.